Rectal Trauma: Evidence-Based Practices - Clemens, Michael S.; Peace, Kaitlin M.; Yi, Fia (Clinics in Colon and Rectal Surgery, 2018)
The management of rectal trauma has often been lumped in with colon trauma when, in fact, it is a unique entity. The anatomic nature of the rectum (with its intra- and extraperitoneal segments) lends itself to unique circumstances when it comes to management and treatment. From the four Ds (debridement, drainage, diversion, and distal irrigation), the management of rectal trauma has made some strides in light of the experiences coming out of the recent conflicts overseas as well as some rethinking of dogma. This article will serve to review the anatomy and types of injuries associated with rectal trauma. A treatment algorithm will also be presented based on our current literature review. We will also address controversial points and attempt to give our opinion in an effort to provide an update on an age-old problem.
Keywords: rectum; rectal trauma; trauma; diversion; drainage